Anorexia e redes sociais: uma análise da comunidade ProAna na perspectiva psicanalítica - Rodrigues, Suzana Viola (Universidade do Vale do Rio dos Sinos, 2019)
The scientific literature on anorexia has considered this eating disturbance as a severe and complex disease. In global ambit, the internet contains sites that propagate and encourage anorexic behavior. This dissertation presents two studies. The first one is a theoretical study which approached the narcissist dimension of anorexia from the point of view of psychoanalysis, and examined the role of the virtual world in this context. The second one is an empirical study with the objective of analyzing manifestations and interactions of the participants of a virtual community who identify themselves as anorexic. The referred community is called ProAna. The method adopted for the research was observational and exploratory and the procedure used was a documental analysis. The data analysis enabled the identification of the following themes: i) ambivalent and narcissist characteristics of the relationship with the mother; ii) the body as the locus of expression of conflict; iii) emotional crutch; iv) awareness of the disease. In the last two mentioned themes, it was possible to recognize some particular categories. Regarding the “emotional crutch” issue, it was observed that anorexia is a way of dealing with difficulties and emotional problems; it makes possible a sense of control and self-efficacy, and to obtain some secondary gains. Concerning the “awareness of the disease”, two categories were identified: one that emphasizes the negative aspects of anorexia, denying the affirmation that it brings benefits, and another that highlights a self-destructive tendency, and manifests pulsation to death. The study made it possible to reveal how crucial issues related to anorexia were expressed in the discussion forum under scrutiny. It is emphasized that anorexia is a complex disorder demanding multi- professional care; it is relevant to articulate studies among the health areas in order to aggregate their efforts to reduce the disorder morbidity and mortality rates. The study of a virtual community such as ProAna may contribute to expand the knowledge about anorexic people and may also supply relevant data to the formulation of a public health policy for the treatment of this population.
Keywords: Anorexia; Narcisismo; Redes sociais; Psicanálise; Narcissism; Social media; Psychoanalysis; ACCNPQ::Ciências Humanas::Psicologia